Membrane Permeabilization Induced by Sphingosine: Effect of Negatively Charged Lipids - Jiménez-Rojo, Noemi (The Biophysical Society, 2014)
Sphingosine [(2S, 3R, 4E)-2-amino-4-octadecen-1, 3-diol] is the most common sphingoid long chain base in sphingolipids. It is the precursor of important cell signaling molecules, such as ceramides. In the last decade it has been shown to act itself as a potent metabolic signaling molecule, by activating a number of protein kinases. Moreover, sphingosine has been found to permeabilize phospholipid bilayers, giving rise to vesicle leakage. The present contribution intends to analyze the mechanism by which this bioactive lipid induces vesicle contents release, and the effect of negatively charged bilayers in the release process. Fluorescence lifetime measurements and confocal fluorescence microscopy have been applied to observe the mechanism of sphingosine efflux from large and giant unilamellar vesicles; a graded-release efflux has been detected. Additionally, stopped-flow measurements have shown that the rate of vesicle permeabilization increases with sphingosine concentration. Because at the physiological pH sphingosine has a net positive charge, its interaction with negatively charged phospholipids (e.g., bilayers containing phosphatidic acid together with sphingomyelins, phosphatidylethanolamine, and cholesterol) gives rise to a release of vesicular contents, faster than with electrically neutral bilayers. Furthermore, phosphorous 31-NMR and x-ray data show the capacity of sphingosine to facilitate the formation of nonbilayer (cubic phase) intermediates in negatively charged membranes. The data might explain the pathogenesis of Niemann-Pick type C1 disease.